Pengaruh Ketersediaan Fasilitas Perpustakaan terhadap Tingkat Literasi Numerasi Mahasiswa Pendidikan Matematika UNIWARA - Ilmiatul Kholifah; Supriyo Supriyo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. This study examines the effect of library facilities and services availability on numeracy literacy among Mathematics Education students at Universitas PGRI Wiranegara (UNIWARA). A quantitative survey design was employed. The sample was selected through purposive sampling, targeting students in at least their fifth semester who had visited the library, resulting in 25 respondents. Data were collected using a questionnaire to capture perceptions of library facilities and service availability and a test to measure numeracy literacy. Data analysis applied simple linear regression using SPSS and was supported by prerequisite tests (validity, reliability, normality, heteroscedasticity, and linearity). The results confirming that library facilities and services significantly influence students’ numeracy literacy. These findings highlight the library’s role as a learning hub that provides curated resources, practice opportunities, and academic support to strengthen numeracy competence in prospective mathematics teachers.